Patrón temporal de vocalizaciones y territorios de descanso del tecolote moteado mexicano (Strix occidentalis lucida Nelson 1903; Strigiformes: Strigidae) en el centro-norte de la Sierra Madre Occidental, México - Rafael-Valdez, Javier; Tarango-Arámbula, Luis Antonio; Martínez-Montoya, Juan Felipe; Equihua-Martínez, Armando; Rosas-Rosas, Octavio Cesar; Olmos-Oropeza, Genaro (Instituto de Ecología, A.C., 2019)
The vocalizations of the Mexican spotted owl (TMM, Strix occidentalis lucida) are essential to maintain an effective and long-distance communication with your partner and neighboring owls, these vary depending on the season and the weather conditions that occur. In addition, their resting territories provide protection from predators and adverse climates. Studying vocalizations, resting places and territories are essential to know the biology of this subspecies with conservation risk. Strix occidentalis lucida is a threatened subspecies due to the loss and fragmentation of its habitats. In Mexico, studies on this subspecies refer mostly to the characterization of their habitat and composition of their diet. Therefore, the objectives of this investigation were: a) to monitor the emission of songs, b) to determine the size of the territories of daytime rest and c) to identify and describe the caves selected by Strix occidentalis lucida to rest. The samplings were conducted seasonally from October 2016 to October 2017 and consisted of monitoring nine pairs of TMM in three regions of the Sierra Madre Occidental. The TMM sang and used caves to rest throughout the year. The average size of its daytime resting territory was 0.81 ± 0.77 ha. This subspecies used the caves more frequently in winter (38.9%) and spring (33.3%). The results of this study are useful to understand the diurnal behavior of the TMM and to design management and conservation plans for the Mexican spotted owl habitat in Mexico.